Some engineering properties of pineapple fruit - Shamsudin, Rosnah; Che Man, Hasfalina; Ariffin, Siti Hajar; Azmi, Nazatul Shima (ISRES Publishing, 2023)
Pineapple is a tropical fruit that is highly relished for its unique aroma and sweet taste. In contrast to other tropical fruits, pineapples typically feature medium-sized fruits with yellow flesh. Based on the physical properties of pineapple fruit variety MD2 such as dimensions, geometric mean diameter (Dg), arithmetic mean diameter arithmetic mean diameter (Da), surface area, volume, sphericity, aspect ratio, and projected area and the best-fit mass models have been determined. From the result obtained, the physical properties such as length, thickness, width, Dg, Da and circumference were found to be 217.8mm, 132.7mm, 132.9mm, 156.5mm, 161.2mm, 394.3mm respectively. Meanwhile for the aspect ratio, mass, volume surface area, sphericity and projected area perpendicular to dimension namely PAL, PAT, AND PAW were found to be 0.61, 1730.4g, 1420 cm3, 77107.4 mm2, 0.72, 22746.0 mm2, 13942.9 mm2, and 16866.3 mm2 respectively. For all physical properties except volume, the best fit mass model to predict mass of pineapple fruits was the quadratic model. Additionally, the findings demonstrated that, in comparison to other attributes, the mass model based on actual volume was more appropriate, with the highest determination coefficient (R2) for Quadratic and S-curve model. For developing and optimizing machinery for handling, maintenance, distribution, and storage, the mass model of pineapple fruits according to the actual volume in the outcomes is relatively important.